Case report: A variant of wall-eyed bilateral internuclear ophthalmoplegia from unilateral pons infarction - Wang, Tingting; Cao, Duanhua; Han, Jingzhe (Frontiers in Neuroscience, 2022)
Wall-eyed bilateral internuclear ophthalmoplegia (WEBINO) is an uncommon ocular motility disorder that encompasses the following clinical signs: bilateral adduction deﬁcits, bilateral abducting nystagmus, convergence lost, and a large angle exotropia in primary gaze. Here we report a case of a 55-year-old man presenting with atypical WEBINO syndrome with unilateral exotropia. The coverage test was used to record the patient's alternating exotropia. The patient experienced diplopia and ophthalmoplegia and was admitted to our hospital three days after the onset of the double vision. Neurologic examination showed left eye exotropia and bilateral internuclear ophthalmoplegia with impaired convergence. Vertical saccades of the left eye were also limited. Consequently, an MRI scan suggested an acute infarction in the left of the pontine tegmentum. The patient was finally diagnosed with pons infarction and was treated with anticoagulation and anti-platelet aggregation therapy.